Conservative management of ovarian endometrioma with sclerotherapy using ethanol prior to in vitro fertilization - Rojas-Ruiz, Juan C (2023)
Ovarian endometrioma is a cyst with ectopic endometrial tissue associatedwith decreased ovarian reserve. Its management in infertility is controversial.We present the case of a 32-year-old woman with decreased ovarian reserveand endometrioma larger than 100 mm. She underwent ultrasound-guidedtransvaginal aspiration and subsequent sclerotherapy with ethanol, achieving a65% reduction in size after three months. Subsequently, in vitro fertilization (IVF)was performed, and pregnancy was achieved. The excision of the endometriomais controversial because it reduces the ovarian reserve. Sclerotherapy has beenshown to preserve ovarian reserve, is associated with a low recurrence rate andfacilitates ovarian accessibility. Ethanol sclerotherapy of endometrioma is a safeand effective outpatient technique that allows pregnancy in women with infertility.